2011
DOI: 10.1093/dnares/dsr006
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic-like Ser/Thr Protein Kinases SpkC/F/K Are Involved in Phosphorylation of GroES in the Cyanobacterium Synechocystis

Abstract: Serine/threonine protein kinases (STPKs) are the major participants in intracellular signal transduction in eukaryotes, such as yeasts, fungi, plants, and animals. Genome sequences indicate that these kinases are also present in prokaryotes, such as cyanobacteria. However, their roles in signal transduction in prokaryotes remain poorly understood. We have attempted to identify the roles of STPKs in response to heat stress in the prokaryotic cyanobacterium Synechocystis sp. PCC 6803, which has 12 genes for STPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 47 publications
(63 reference statements)
1
25
0
2
Order By: Relevance
“…In the genome of the model unicellular cyanobacterium Synechocystis sp. PCC6803 (hereafter Synechocystis 6803), seven genes, spkA–spkG , have been predicted to encode for the S/T protein kinases of the Pkn2 family, and five genes, spkH–spkL , for the ones of the ABC1 family . SpkA is involved in the control of cell motility by regulating expression of pili family genes .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the genome of the model unicellular cyanobacterium Synechocystis sp. PCC6803 (hereafter Synechocystis 6803), seven genes, spkA–spkG , have been predicted to encode for the S/T protein kinases of the Pkn2 family, and five genes, spkH–spkL , for the ones of the ABC1 family . SpkA is involved in the control of cell motility by regulating expression of pili family genes .…”
mentioning
confidence: 99%
“…Zorina et al . demonstrated that SpkC, SpkF and SpkK are involved in phosphorylation of the small chaperonin GroES. However, regulation, function, and substrate recognition of Synechocystis 6803 S/T protein kinases remain poorly investigated .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, SpkE lacks several key amino acids that are necessary for ATP binding and is not a true protein kinase (15). In addition, there are five putative kinases of the ABC1-type, named SpkH through L (50). The functions of a few cyanobacterial Ser/Thr kinases have been addressed through phenotypical characterization of the respective mutants.…”
Section: Innovationmentioning
confidence: 99%
“…SpkG can sense high-salt stress signals directly (Liang et al, 2011), and spkG was found to be highly down-regulated in iron defi ciency under peroxide stress (Singh et al, 2004). In addition, SpkC, SpkF, and SpkK work one after the other to fi nally phosphorylate the co-chaperonin GroES (Zorina et al, 2011).…”
Section: Introductionmentioning
confidence: 99%